1991
DOI: 10.1080/09540129108253056
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and rewards of being an AIDS emotional-support volunteer: A scale for use by care-givers for people with AIDS

Abstract: This study describes scales which can be used to identify the levels of stress and reward associated with being a AIDS emotional-support volunteer. Four categories of stressors were identified. These were 'emotional overload', 'client problems', 'lack of support' and 'lack of training'. The reward categories were 'personal effectiveness', 'emotional support', 'social support' and 'empathy/self-knowing'. There were low, but positive correlations between these stressor scales and other measures of psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…Ross and Seeger (1988), and Bennett, Miller and Ross (1995) identified that HIV/AIDS workers gain a great deal of satisfaction from their work. Guinan, McCallum, Painer, and Dykes (1991) and Kleiber, Enzmann, and Gusy (1995) relayed that HIV/AIDS workers had a greater sense of personal and professional accomplishment than other workers in health care, such as those who work with the elderly or cancer patients. Hoffman (1997) identified that HIV/AIDS counselors experienced both stressors and rewards in the course of their work.…”
Section: Counselor Meaningmentioning
confidence: 96%
See 1 more Smart Citation
“…Ross and Seeger (1988), and Bennett, Miller and Ross (1995) identified that HIV/AIDS workers gain a great deal of satisfaction from their work. Guinan, McCallum, Painer, and Dykes (1991) and Kleiber, Enzmann, and Gusy (1995) relayed that HIV/AIDS workers had a greater sense of personal and professional accomplishment than other workers in health care, such as those who work with the elderly or cancer patients. Hoffman (1997) identified that HIV/AIDS counselors experienced both stressors and rewards in the course of their work.…”
Section: Counselor Meaningmentioning
confidence: 96%
“…Reports of HIV/AIDS counselor burnout in Australia, Eritrea, Ghana, India, Kenya, Malawi, South Africa, Thailand, and Zambia, indicate that burnout may be a common occurrence, particularly for those who lack counselor support and/or supervision (AIDS Analysis Africa, 1995;Boswell et al, 2002;Maria, Paranthaman, & Nanmozhi, 2002;and Taegtmeyer et al, 2002). Taegtmeyer et al (2002) and Guinan, McCallum, Painer, and Dykes (1991) indicated that the use of counselor support and supervision could reduce burnout and increase the quality of the counseling services provided. However, supervision in Zimbabwe may be less available than support services.…”
Section: Counselor Supportmentioning
confidence: 97%
“…137± 143), and conducted additional analyses of these data to exam ine the relationsh ip betw een stressors, rewards and burnout. Guinan et al (1991) developed a scale (H IV Volunteer Inventory) to m onitor the levels of stress in HIV/AIDS volunteers. Four prim ary stressor factors (Stress1± Stress4) were obtained using factor analysis:…”
Section: Ethodsmentioning
confidence: 99%
“…It would appear important to carry out m ore qualitative work in volunteers to determ ine whether burnout is a useful concept to use in volunteers or whether it needs to be m odi® ed in this population. The work of Guinan et al (1991) suggests that th e dimensions of stresses and rewards in volunteers m ay include states related to em otional exhaustion, depersonalization and personal achievem ent.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the four stressor factors, four reward factors are also m easured on the HIV Volunteer Inventory: (1) Personal effectiveness indicates the volunteer' s perception of th e effectiveness of their work; (2) Em otional support describes the volunteer' s emotional support from inside and outside th e organization; (3) Social support identi® es satisfying social activities; and (4) Em pathy /self-knowing refers to the personal growth of the volunteers and their em pathy for their clients. The HIV Volunteer Inventory was validated by the signi® cant positive correlations with tw o standard m easures of psychological m orbidity (GH Q and M BI) (Guinan et al, 1991).…”
Section: Introductionmentioning
confidence: 99%